Supervision of Village Financial Management by Kotamobagu City Inspectorate - Isriani; Bogar, Wilson; Mokat, Jetty H. E. (Technium Social Sciences Journal, 2025)
The purpose of the study was to determine, analyze and describe the Supervision of Village Financial Management by the Kotamobagu City Inspectorate and the determinants of the use of the Siswaskeudes Application in carrying out village financial management supervision. The method used in this research is qualitative research method. As for the results of the study, namely in the implementation of Supervision with the Village Financial Supervision Information System (Siswaskeudes), there are four important indicators, namely (1) Planning is the planning of village government revenues and expenditures in the desired fiscal year budgeted in the APBDes and RPJM-Village and RKP-Village. in a transparent, accountable, participatory, and orderly and disciplined budget. (2) Implementation with the Village Financial Supervision Information System (Siswaskeudes) is carried out with a risk-based approach and Computer-Aided Audit Techniques (TABK). Siswaskeudes is an innovation that aims to examine village financial management in a transparent, effective and efficient manner. (3) Reporting on the Results of Supervision of Village Financial Management at least contains findings in Village Financial Management and recommendations for improvements to be followed up by the Village Government and the Audit Report is reviewed in stages and signed by inspectors according to their respective authorities no later than 2 (two) weeks after the supervision is completed and submitted to the central government. (4) Follow-up of village financial management with the Village Financial Monitoring System (Siswaskeudes) is part of the reporting output generated from the Findings Recapitulation Application which presents information on findings, criteria, causes, consequences, suggestions, responses, and follow-up.